Phantasmatic Entities and Identities: Criminals without Guilt in Colombia (2018)
In this article, I examine some experiences drawn from the ethnographic fieldwork I have done over many years in Colombia–a country that has endured a violent armed conflict for over 60 years, leaving thousands of dead and disappearedand discuss some theoretical propositions around these experiences. Taking as a starting point an obscure folk metaphor described by a hitman (sicario) in the emerald-mining region of the country, I refer to the figure of the Phantom as put forward by French psychoanalyst Jacques Lacan in his Seminar 14 (‘The Logic of the Phantom/ Phantasm’), and to the figure of the masked wrestler of Mexican urban folklore. I analyse the widespread use by Colombian criminals of performative resources and alternate names, which allows them to fluctuate between legality and illegality without assuming the consequences of their actions. Maintaining different phantasms to obscure the secret pleasure they derive from their actions has been one of their ways of being in the world. As I intend to show, this procedure enables some criminals to alternate between different subjective positions in order to camouflage and conceal not only their criminal acts but also the reality of their desires and their guilt.